Acidic Hydrogen-Tethered Electron-Deficient Acceptors for Phosphine-Catalyzed Annulations - Zhou, Leijie; Guo, Hongchao (Synlett, 2024)
Nucleophilic phosphine-catalyzed annulations are recognized as practical and powerful tools for synthesizing various cyclic compounds. Phosphine acceptors play a key role in nucleophilic phosphine catalysis. The design and synthesis of new phosphine acceptors that are able to introduce new zwitterionic intermediates with new reactivities into phosphine-catalyzed annulations is highly desirable. We recently applied proton-shift principles in the design of new phosphine acceptors, and we synthesized several new acceptors. With the use of these acceptors, we have developed several novel phosphine-catalyzed annulation reactions. In this account, we present a brief introduction to the design and application of a series of acidic-hydrogen-tethered electron-deficient acceptors for phosphine-catalyzed annulation reactions, categorized according to the type of atom (N–H, O–H, C–H) to which the acidic hydrogen is bound.1 Introduction2 Phosphine Acceptors Tethered with an Acidic N–H Group3 Phosphine Acceptors Tethered with an Acidic O–H Group4 Phosphine Acceptors Tethered with an Acidic C–H Group5 Conclusions
Keywords: phosphine catalysis; annulation; cyclic compounds; acidic hydrogen; phosphine acceptors